Locally Recurrent Prostate Cancer after External Beam Radiation Therapy: Diagnostic Performance of 1.5-T Endorectal MR Imaging and MR Spectroscopic Imaging for Detection(1) - Westphalen, Antonio C. (Radiological Society of North America, Inc., 2010)
PURPOSE: To determine if performing magnetic resonance (MR) spectroscopic imaging, compared with performing T2-weighted MR imaging alone, improves the detection of locally recurrent prostate cancer after definitive external beam radiation therapy. MATERIALS AND METHODS: This retrospective single-institution study was approved by the committee on human research, with a waiver of informed consent, and was compliant with HIPAA requirements. Sixty-four men who underwent endorectal MR imaging, MR spectroscopic imaging, and transrectal ultrasonographically guided biopsy for suspected local recurrence of prostate cancer after definitive external beam radiation therapy were retrospectively identified. Thirty-three patients had also received androgen therapy. Recurrent cancer was determined to be present or absent in the left and right sides of the prostate at T2-weighted MR imaging and MR spectroscopic imaging by a radiologist and a spectroscopist, respectively. Area under the receiver operating characteristic curve (A(Z)) was calculated for T2-weighted MR imaging alone and combined T2-weighted MR imaging and MR spectroscopic imaging by using generalized estimating equations and by using biopsy results as the reference standard. RESULTS: Recurrent prostate cancer was identified at biopsy in 37 (58%) of the 64 men. Recurrence was unilateral in 28 patients and bilateral in nine (total of 46 affected prostate sides). A(Z) analysis revealed that use of combined T2-weighted MR imaging and MR spectroscopic imaging (A(Z) = 0.79), as compared with T2-weighted MR imaging alone (A(Z) = 0.67), significantly improved the detection of local recurrence (P = .001). CONCLUSION: The addition of MR spectroscopic imaging to T2-weighted MR imaging significantly improves the diagnostic accuracy of endorectal MR imaging in the detection of locally recurrent prostate cancer after definitive external beam radiation therapy. © RSNA, 2010